Facilitators and Barriers to Resident Physical Activity Participation in Rural Long-term Care Facilities: A Facility Perspective - Marstall, Kendra (My University, 2024)
Background – Physical activity (PA) within long-term care (LTC) environments is often low for a variety of reasons, but few studies have reviewed this through a rural geographic lens. This study aimed to understand the facilitators and barriers to resident PA participation in rural LTC from a facility perspective. A secondary aim was to understand strategies to promote resident PA within rural LTC. The administrative focus gives the opportunity to understand factors impacting PA from the facility level. Methods – Using a mixed methods study design, both quantitative and qualitative data were collected in fall 2023 via surveys (n=31 facilities) and interviews (n=10 individuals) from individuals holding administrative positions (e.g., administrator, activities coordinator, director of nursing) in rural LTC settings across the state of Kansas. Survey items assessed facilitators on a 5- point Likert scale (1 = strongly disagree) to (5 = strongly agree). Respondents ranked barriers from (1 = not at all a barrier) to (4 = major barrier) and gave feedback on what would help promote PA participation from (1 = not at all helpful) to (5 = extremely helpful). Descriptive statistics were used to evaluate results from the survey. Thematic analysis was used to analyze interview findings, following an iterative process with two independent coders. Results – Survey respondents agreed that provision of PA equipment (4.23±0.92/5), staff training (3.77+1.05/5), and dedicated staff and volunteers (3.68±1.22/5) were current facilitators of PA. Results showed that staffing shortages (2.35±0.84/4), insufficient funding (2.16±1.07/4), and absence of space (2.06±1.03/4) were minor barriers to resident PA participation. Data indicated that additional staffing (4.13±0.76/5), increased funding (3.94±1.21/5), greater family and resident involvement (3.94±1.03/5), as well as more outdoor opportunities for PA (3.90±1.08/5), enhanced PA programming (3.77±1.15/5), and dedicated space (3.58±1.15/5) would be helpful in improving resident PA participation in rural LTC. Interviews revealed four main themes: PA facilitators, PA barriers, facility approach to PA, and current PA levels. Interview findings supported what was found in the surveys and expanded upon initial findings. Notably, staffing, lack of resident motivation, and resident health status were frequently discussed barriers to PA. In addition to staff encouragement and collaboration, making PA enjoyable through gamification, outdoor activities, and the inclusion of music emerged as a potential facilitator of resident PA. Conclusions –This study identified important facilitators and barriers that may help promote resident PA participation in rural LTC facilities. Findings can support intervention development to increase PA and improve the health of residents living in rural LTC.
Keywords: Physical activity; Long-term care; Rural; Aging; Facilitators and barriers